Economic feasibility study of the establishment of smallholder pig farmers for the commercial market : Empolweni case study - Roelofse, Johannes Jacobus (Hanno) (Stellenbosch : Stellenbosch University, 2013)
Thesis (MScEng)-- Stellenbosch University, 2013.